Агаарын нөлөөг тооцсон хэвтээ чиглэлд шидэгдсэн биеийн хөдөлгөөн хамгийн хол тусах өнцөгийн бодолт - Пүрэвдорж, Мөнхбаяр (Scientific transaction of the National University of Mongolia. Physics, 2022)
In this paper, the air resistance force in the projectile motion has been considered. The maximum distance of projectile can be analyzed with effects of air resistance.